The Disability Studies Reader. - Davis, Lennard J. (Taylor and Francis, 2013)
The Fourth Edition of the Disability Studies Reader breaks new ground by emphasizing the global, transgender, homonational, and posthuman conceptions of disability. Including physical disabilities, but exploring issues around pain, mental disability, and invisible disabilities, this edition explores more varieties of bodily and mental experience. New histories of the legal, social, and cultural give a broader picture of disability than ever before. Now available for the first time in eBook format 978-0-203-07788-7.